Challenges of quality assurance of software developed by a subcontractor : a case study - Erme, Harri (2024)
Outsourcing of software development to subcontractors has been a popular business strategy for a long time. Subcontracting at its best enables acquisition of missing competencies, dampening of demand fluctuations, and cost savings due to the subcontractor's benefits from economies of scale. However, it's important to carefully assess a subcontractor's capabilities, as a poorly managed subcontracting relationship can cause significant issues in quality and delays delivery timelines. Quality problems in particular can widely affect the cooperation between the client and subcontractor. The risks have materialized in the case company of this thesis, where unexpectedly significant quality issues have led to slow and difficult quality assurance processes. This thesis conducts a case study in an international IT company in order to map out the challenges the case company has experienced in the subcontracting relationship from the perspective of software quality assurance. Additionally, solutions to these problems are explored by interviewing employees of the case company. The empirical part of the thesis results in a comprehensive and categorized collection of challenges and solutions. Based on these findings, the target company, as well as other organizations in a similar situation, can create a strategy and take actions to start improving the subcontracting relationship. The study was conducted using qualitative research methods. Data was collected by interviewing employees of the case company in focus groups. Semi-structured interviews covered different phases of quality assurance, after which the transcribed data was analyzed. Content analysis revealed a total of 28 challenges and 20 solutions. Many of the identified problems can be traced back to the subcontractor. On the other hand, the target company itself has its own problems but also the capabilities to correct them. For example, by focusing particularly on requirements engineering, the target company can create better conditions for the subcontractor to produce higher quality software.